2023
DOI: 10.3389/fimmu.2023.1125794
|View full text |Cite
|
Sign up to set email alerts
|

Novel murine model reveals an early role for pertussis toxin in disrupting neonatal immunity to Bordetella pertussis

Abstract: The increased susceptibility of neonates to specific pathogens has previously been attributed to an underdeveloped immune system. More recent data suggest neonates have effective protection against most pathogens but are particularly susceptible to those that target immune functions specific to neonates. Bordetella pertussis (Bp), the causative agent of “whooping cough”, causes more serious disease in infants attributed to its production of pertussis toxin (PTx), although the neonate-specific immune functions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Additionally, they can be activated independently of antigens, instead rapidly expanding after cytokine signaling [ 21 , 69 ]. These are observed in highest amount at P8 and are greatly reduced by P10, suggesting they are a significant component of the neonatal immune system [ 70 ]. Neonatal mice also have populations of regulatory T cells (Tregs) which are primarily anti-inflammatory and produce TH2 cytokines and responses.…”
Section: The Neonatal Immune System Is Composed Of Unique Cellsmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, they can be activated independently of antigens, instead rapidly expanding after cytokine signaling [ 21 , 69 ]. These are observed in highest amount at P8 and are greatly reduced by P10, suggesting they are a significant component of the neonatal immune system [ 70 ]. Neonatal mice also have populations of regulatory T cells (Tregs) which are primarily anti-inflammatory and produce TH2 cytokines and responses.…”
Section: The Neonatal Immune System Is Composed Of Unique Cellsmentioning
confidence: 99%
“…MDSCs (discussed above) have a primary role in T cell suppression [ 65 ]. Despite this, it was observed that P5 mice inoculated with a mutant of B. pertussis had an influx of neutrophils into the lungs, followed by T cells at 1 dpi (P6) [ 70 ]. However, it has also been observed that T cells are defective in migrating to neonatal alveolar spaces in lungs [ 28 ].…”
Section: The Neonatal Immune System Is Composed Of Unique Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…This apparent failure, and the later transition to a more adult-like immune system, support a common view that the neonatal immune system (NIS) is an incompletely developed version of the adult immune system. However, newer work suggests that rather than being simply deficient, the NIS has different, and in some cases more effective, responses than the adult immune system (AIS), with the potential for vigorous responses being more tightly controlled ( 1 , 2 ). These neonatal-specific responses, believed to prevent damaging inflammation, appear to contribute to the increased susceptibility of neonates to a subset of pathogens.…”
Section: Introductionmentioning
confidence: 99%